Safety and efficacy of COVID-19 vaccines in children and adolescents with cancer - Nilgün Kurucu; Tezer Kutluk; İbrahim Kartal; Şule Yeşil; Özge Vural; Oğuz S. Dinçer; Mehmet Ceyhan (The Turkish Journal of Pediatrics)
Background. Children with cancer have a higher morbidity and mortality due to COVID-19. Vaccination of children with cancer is important. In this study, we aimed to investigate the effectiveness and side effects of the COVID-19 vaccines in children and adolescents with cancer.